Penerapan Pemberian Minyak Zaitun pada Pasien Gagal Ginjal Kronik dengan Resiko Gangguan Integritas Kulit yang Menjalani Hemodialisis: Application of Olive Oil Administration in Chronic Kidney Failure Patients at Risk of Skin Integrity Impairment with Hemodialysis - Rama Danita, Putri; Yanti, Sri; Kharisna, Dendy; Hasanah, Ulfa (Universitas Ngudi Waluyo, 2025)
Chronic kidney failure (CKF) occurs when the kidneys experience a decline in their function and duties. This condition affects various body systems, leading to fluid imbalances, edema, increased blood pressure, and heart rhythm disturbances. One of the replacement therapies is hemodialysis. However, hemodialysis can also lead to clinical complications, one of which is uremic pruritus, a chronic itching sensation often experienced by patients that impacts their comfort and quality of life. One non-pharmacological intervention that can be applied to address this complaint is the use of olive oil as a natural moisturizer, which functions to reduce pruritus and improve skin condition. This study aims to describe the administration of olive oil to chronic kidney failure patients at risk of skin integrity impairment. The intervention was implemented using a case study method with an Evidence-Based Nursing (EBN) approach on 5 patients. The intervention was performed twice, once a day for 5 minutes. Evaluation was conducted using the Pruritus Severity Scale (PSS) questionnaire. The results showed a significant decrease in pruritus scale and improvement in skin condition after the administration of olive oil. The application of this therapy has been proven effective in reducing the risk of skin integrity disorders in CKF patients undergoing hemodialysis.